2011
DOI: 10.3109/11038128.2011.569757
|View full text |Cite
|
Sign up to set email alerts
|

Getting used to assistive devices: Ambivalent experiences by frail elderly persons

Abstract: The aim was to learn how frail elderly people experienced becoming assistive device users and how assistive devices affected their independence in daily activities. Focus-group methodology was used, including people 80 and older with multiple health problems. Five group discussions were conducted with a total of 18 people including 14 women and four men. Each group met once, for 90-120 minutes, and all discussions were audiotaped. Two themes emerged: Confidence in knowledge and experience and getting used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 37 publications
1
46
0
Order By: Relevance
“…The reason for this is not known, but it has been suggested that environmental factors might be a contributing factor (7). The physical and social environment is known to both promote and limit the use of assistive devices in general, and the integration of the device in the user's context is important (9). Yet, studies of PMDs do not often simultaneously consider personal, environmental and occupational aspect (7), even if this has been advocated for (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is not known, but it has been suggested that environmental factors might be a contributing factor (7). The physical and social environment is known to both promote and limit the use of assistive devices in general, and the integration of the device in the user's context is important (9). Yet, studies of PMDs do not often simultaneously consider personal, environmental and occupational aspect (7), even if this has been advocated for (10).…”
Section: Introductionmentioning
confidence: 99%
“…Struggling to include the PMD as part of everyday occupations 9 The men who used PW discussed how they at first did not want to have PWs and leave their manual wheelchairs, since they saw it as a sign of failure and of decline. Their own reflections were that they had been stubborn and had wanted to manage everyday occupations without a PW, and how they had struggled before they had come to realize that they should have had it earlier.…”
Section: Struggling To Be An Independent Pmd Usermentioning
confidence: 99%
“…Becoming accustomed to an ATD is a process in which the users' own perception of needs, as well as social and physical contexts, influence the experience [16]. The meaning attributed to ATDs is influenced by the users' perceived difficulties, perceived faith in being well-served by the device, and perception regarding whether it corresponds to or challenges their self-image [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that starting to use an ATD may be a complex process for the older individual that may involve an ambivalent experience, negotiation and a transition period of adjusting to the ATD (14,15). To facilitate client-centred ATD service delivery, the occupational therapist should work in a close and collaborative relationship with the client during all stages of the service delivery process (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%